Promoting Livelihood Opportunities in Rural Areas through Sustainable Tourism: A Sustainable Livelihood Approach - Alam, Iftekhar (International Journal of Social Sciences and Management, 2025)
The tourism sector is poised for significant expansion throughout the country. Supported by prior research, developing sustainable tourism stands out as a critical strategy for poverty alleviation. Sustainable tourism generates livelihood opportunities, stimulates the local economy, enhances community assets, drives infrastructural development, and ensures environmental protection. These elements are essential for improving the well-being of residents, reducing vulnerability, and promoting a more responsible use of natural and other resources within communities. While the discourse on sustainable tourism has gained momentum over the past few decades, insufficient attention has been dedicated to its role in tackling key issues like sustainable livelihoods and overall well-being. This study decisively utilizes the “Sustainable Livelihood Framework (SLF)” developed by the Department for International Development (DFID) to analyze the impact and relationships among its core components—vulnerability context, livelihood assets, structures, and processes—in promoting livelihood opportunities in rural areas through sustainable tourism. The insights from this paper underscore the critical importance of these SLF components, which connect in a non-linear fashion, and their implications for effective livelihood interventions. Moreover, the abundant social capital present in rural areas must be strategically harnessed to create enhanced livelihood opportunities. Int. J. Soc. Sc. Manage. Vol. 12, Issue-3: 123-131.